Analisis Penerapan Standard Recipe Menu Coffee Break dalam Menjaga Konsistensi Biaya Produksi Bakery Hotel Santika Kelapa Gading - Frisca Sasri Dwitama; Feri Ferdian; Yasri Yasri; Elida Elida (Lembaga Yasin AlSys, 2026)
Although food cost control has been widely discussed in hospitality research, studies that specifically examine the consistency of standard cost ratios across coffee break menus based on standard recipe documents remain limited. This study aims to analyze the implementation of standard recipes and identify the consistency of food cost ratios in the coffee break menus of Hotel Santika Kelapa Gading. This study used a descriptive quantitative approach with a case study design. The units of analysis consisted of three standard recipe documents for the bakwan, fried cassava, and chicken curry noodle menus, which were purposively selected based on the completeness of cost data. Data were collected through documentation and analyzed using descriptive analysis and simple statistics with the assistance of RStudio. The results showed that the three menus had different total production costs, minimum selling prices, and net revenues, but produced a rounded food cost ratio of 25%. The RStudio-assisted analysis showed a mean value of 25% and a standard deviation of 0. These findings strengthen the understanding of the relationship between recipe standardization, cost-per-portion calculation, and selling price determination in production cost control. The conclusion of this study affirms the importance of standard recipes as a basis for controlling standard cost ratios in coffee break menus. The implications of this study provide practical contributions for hotel management in maintaining production cost consistency and open opportunities for further research comparing standard food cost and actual food cost across several production periods.